2010
DOI: 10.1128/jcm.02459-09
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Mycobacterium tuberculosis Drug Susceptibility Testing and Genotyping with Epidemiological Data Analysis To Gain Insight into the Epidemiology of Drug-Resistant Tuberculosis in Malatya, Turkey

Abstract: Drug-resistant tuberculosis (TB) presents a major challenge to global TB control. To gain a better understanding of drug-resistant TB epidemiology in Malatya, Turkey, we conducted the present study using 397 Mycobacterium tuberculosis clinical isolates collected from Malatya, Turkey, in recent years (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007). Resistance to any anti-TB drug was found in 29% (114 of 397) of the study isolates, while the multidrug resistance (MDR) rate was ϳ4.5% (18 of 397). Resistances to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
3
1
Order By: Relevance
“…A study of Nepal 2017 reported a relatively higher prevalence of resistance to one or more drugs (38.2%) in comparison with our study, but the prevalence of MDR (11.7%) and the resistance to RIF (15.7%) were lower in their investigation than the results of our survey [17]. Also in another study in Turkey in 2010 comparing to our study, a lower rate of prevalence resistance (28.7%), MDR (4.5%) and resistance to RIF (6.3%) were reported [18].…”
Section: Discussioncontrasting
confidence: 83%
“…A study of Nepal 2017 reported a relatively higher prevalence of resistance to one or more drugs (38.2%) in comparison with our study, but the prevalence of MDR (11.7%) and the resistance to RIF (15.7%) were lower in their investigation than the results of our survey [17]. Also in another study in Turkey in 2010 comparing to our study, a lower rate of prevalence resistance (28.7%), MDR (4.5%) and resistance to RIF (6.3%) were reported [18].…”
Section: Discussioncontrasting
confidence: 83%
“…In recent years, about 2-64% of MDR M. tuberculosis has been reported between 2000 and 2014 in different countries of the world and in different regions of our country. It is also stated that the rate of MDRs is low in new cases but it can be increased because of the use of antibiotics in patients who have already received TB treatment (1,2,4,5,(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of M. tuberculosis (MTB) resistance to anti-TB drugs has been a major public health obstacle to achieve the goal of effective global TB control [1]. Drug resistance in M. tuberculosis isolates arises from spontaneous genetic mutations and can be enhanced by poor adherence of patients to anti-TB drugs [2]. Multidrug resistant TB (MDR-TB) portrays a very grave danger and particularly challenging to treatment interventions while Extensively drug resistance TB (XDR-TB) is virtually untreatable and should by all means be avoided.…”
Section: Introductionmentioning
confidence: 99%